Vloga urbanističnega oblikovanja pri notranjem razvoju naselij - Dimitrovska Andrews, Kaliopa (Urbani izziv, 2005)
In contemporary urbanistic practise internalised city development is proving to be one of the most sustainable forms of city development and has many advantages over urban expansion onto virgin land. Besides all advantages it nevertheless triggers numerous dilemmas, how new buildings should be placed inalready formed urban environments without causing aesthetic or functional degradation and simultaneously wouldn't deny legitimate investment expectations concerning profitability. The article deals with methodology for assessing and stimulating urban design criteria and economic efficiency of projects in development/rehabilitation of urban sites. The method's utility isshown by analysis of cases of substitute or infill developments in Ljubljana(multi-apartment building on Gradaška street and the Condominium in Trnovski pristan), whose unconventionality attracted the wider public's attention, but from the urban design aspect in many ways disregard the place'spresent character.
Keywords: aesthetics; estetika; mesta; oblikovanje; raba prostora; urbani razvoj; urbanistično planiranje